IMPORTANCE OF HIJAB THROUGH SOCIAL MEDIA COMMENT - Shikha, Farzana Afrin; Hoque , Ashikul; Hasanat, Mohammad Waliul; Akter, Shahanaz; Hamid, Abu Bakar Abdul (International Journal of Psychosocial Rehabilitation, 2020)
There are a considerable amount of controversies regarding ethnic dress like hijab as many raise questions about the importance of the hijab among the Muslim community. The paper sheds light on several social media comments on the hijab in the Muslim community. The significance of hijab like ethnic dresses has been evaluated through social media comments on several media websites. The comments related to ethnic dresses show that awareness among people about cultural diversity has been increasing significantly. The social media comments about the hijab are important evidence that the concern about ethnic attire, social cohesion, and cultural differences are increasing among the people. The paper provides adequate emphasis on the meaning of hijab or veiling. The main objective of the paper is to provide an effective evaluation of the attire of Islamic populations and the social media reactions on this attire. Several previous articles of renowned authors who have worked in this matter are carefully evaluated to get ideas about this matter.